The relevance of the participation of the environmental expert in the composition of the conduct adjustment term (Research, Society and Development, 2023)
Environmental damage is increasingly emerging due to accelerated technological evolution which often creates new risks for society. In the legal sphere, environmental conflicts demand effective solutions aimed at repairing or preventing damage to property, rights or meta-individual interests. The conduct adjustment term (TAC) therefore stands out as an appropriate means of resolving disputes in the environmental field, speeding up the solution of cases involving environmental protection. The aim of this research is to assess the expert technical contribution relevance in the conclusion of conduct adjustment agreement and their contribution to the density of the definition of the technical specificity clauses of the commitment. The methodological approach used was a bibliographical survey and legislative research. As a result, it was demonstrated the significance of the technical expert participation in the definition of the technical specificity conduct adjustment agreement clauses, as well as the positive effects of this contribution, such as increased engagement and adherence by the interested party to comply with them.